(untitled) (Journal Of Educational and Psychological Researches, 2018)
The study intends to explore the obstacles that encounter a program of rehabilitating released prisoners as perceived by prisoners themselves in tubas’ province. To this end, the researcher used a questionnaire as an instrument which was applied on (150) prisoner had chosen randomly to collect the study data. The findings revealed no significant differences among obstacles the encounter program regarding to the following variables: age, detention period, and number of detention, additionally, the findings found that there is a variance of obstacles mean according to the prisoners themselves, rehabilitation program, and the facility of that program.